Early removal of odontoma resulting in spontaneous eruption of the impacted teeth - Achmad Harijadi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2010)
Background: Compound odontomas in the anterior maxilla during mixed dentition frequently cause obstruction to the eruption pathway of permanent upper anterior teeth. Removal of the odontomas may or may not lead to spontaneous eruption of the impacted teeth depending on the age when the surgery is performed, the size of the lesion, and the stage of tooth development of the involved teeth. Purpose: This paper attempts to emphasize the importance of early removal of compound odontoma to enable spontaneous eruption of the affected teeth. Case: A case of odontoma in the anterior maxilla causing failure of eruption and delayed root formation of upper right permanent lateral incisor and canine in a 10-year-old male patient is presented. Case management: The odontoma was surgically removed under general anesthesia and histology result confirmed the diagnosis of compound odontoma. A three-year post surgical follow up showed spontaneous eruption as well as continued root formation of the two affected teeth. Conclusion: Removal of odontoma may lead to spontaneous eruption of the affected teeth if their root development are not completed.Latar belakang: Compound odontoma pada daerah anterior maksila pada masa geligi pergantian sering menyebabkan hambatan erupsi pada gigi permanen penggantinya. Kemungkinan terjadinya erupsi spontan gigi permanen yang impaksi setelah pengambilan odontoma tergantung dari: umur penderita pada saat dilakukan operasi, ukuran lesi odontoma dan tahapan perkembangan gigi permanen yang terlibat. Tujuan: Laporan kasus ini ingin menekankan pentingnya pengambilan compound odontoma sedini mungkin untuk memberi kesempatan tumbuhnya gigi permanen yang terlibat dan erupsi secara spontan. Kasus: Ditampilkan sebuah kasus compound odontoma pada regio maksila anterior menyebabkan gagalnya erupsi dan terlambatnya pembentukan akar gigi insisif kedua dan kaninus permanent rahang atas kanan pada penderita anak laki-laki berumur 10 tahun. Tatalaksana kasus: Dilakukan eksisi odontoma dengan pembiusan umum dan pemeriksaan histopatologi menunjukkan lesi tersebut adalah compound odontoma. Dalam kurun waktu 3 tahun pasca pembedahan kedua gigi permanen yang impaksi dapat erupsi sempurna secara spontan disertai dengan berlanjutnya proses pembentukan akar. Kesimpulan: Pengambilan odontoma dapat menyebabkan erupsi secara spontan gigi permanen yang impaksi dengan syarat proses pembentukan akar gigi yang bersangkutan belum selesai.